Economic evaluation and energy/exergy analysis of PV/Wind/PEMFC energy resources employment based on capacity, type of source and government incentive policies: Case study in Iran. (February 2021) - Mostafa Nosratabadi, Seyyed; Hemmati, Reza; Bornapour, Mosayeb; Abdollahpour, Mostafa
Highlights: The economic evaluation of using the renewable energy resources is performed. The PV power, wind power, and fuel cell unit resources are analyzed in Sirjan city, Iran. Three different scenarios based on the installed capacity, resources type and government policies is considered and analyzed. Different situation of PV panels and wind turbines are studied and the best one is selected. Energy and exergy analysis is performed to better understanding the efficiencies value of resources. Abstract: The energy supply concerns are increased with the increment of demand, environmental emission, and global warming. As an alternative to fossil fuels, the development of renewable energy technologies is one of the most important strategies. Thus, governments around the world have adopted policies to expand the share of clean energy with a view to the greenhouse gas (GHG) emissions reduction and many other policies. In this study, the economic evaluation and energy/exergy analysis of using renewable energy resources (wind, solar, and fuel cell) has been performed under three scenarios in Sirjan city, Iran. The studied scenarios are distinguished from each other due to the capacity to be installed, renewable energy sources type, and different work policies. Related to the photovoltaic (PV) and wind energy, different types of PV panels and wind turbines are studied, and the most favorable one is selected. Also, the best way is considered to install PV panels and fuel cells in this location based on different policies. According to this, it can be said that the economic aspects of the investigation are clarified and studied in renewable energy under the policies and scenarios for investors in this field.